Implementation of foundation CSS framework on the Development of a Food Order System to cater for different devices / Muhammad Nur Afiq Radzizul - Radzizul, Muhammad Nur Afiq (2017)
This research is about implementation of a CSS Foundation Framework on the Development of Food Order System to cater for different devices. This research is to encounter the problem of one of the restaurant in Kuala Lumpur. Teratak Selera is the name of the restaurant. This research is to give exposure about the element that suitable and can be used to implement on the product in this research to cater it requirement. The element is needed in the research because this is to ease the user in handling the product. To find the suitable element in this research, literature review is done to the element. This study gives much kind of element that is existed and suits with the research. An element is chose to help in making research done. This research is using a waterfall methodology where this research has four phases and each phases contain the activities required and the activities that need to be done by the researcher. All phases have its objectives. To achieve the objectives of this research, all activities required in each phases is need to be done by the researcher. By completing the activities in the research methodology there are deliverables that is produced. All the deliverables produced are the results and founding of the research. All deliverables is recorded in the document. There are many new things that have been discovered in doing this research. This research can be extended due to the new researchers that want to continue this research by adding research scope or studying on new complexity of the research.